The impact of a gender mainstreaming-based blended learning flipped classroom model on the solidarity values and problem-solving abilities of students - Kasmini, Lili; Mardhatillah; Prayudi, Satria (International Journal of Innovative Research and Scientific Studies, 2024)
This study examines the impact of a gender mainstreaming-based blended learning flipped classroom model on the solidarity values and problem-solving abilities of students. The acquisition of problem-solving skills and the cultivation of values related to solidarity are imperative proficiencies in the context of 21st-century dynamics. These competencies serve as pivotal attributes for students aspiring to navigate the intricacies of communal and national challenges. An existing quandary lies in the domain of primary education within the Aceh province, and the pedagogical landscape within primary schools has not incorporated the essential dimension of nurturing adeptness in problem-solving. This is because learning is still teacher-centered and needs more student engagement. Therefore, a model should be developed to address the issue of gender mainstreaming-based blended learning in a flipped classroom model. This research aims to develop a model for developing a blended learning flipped class based on gender mainstreaming to increase students’ solidarity values ​​and problem-solving abilities. This study employed a development model that referred to the 4-D model proposed by S. Thiagarajan et al., consisting of definition, design, development, and dissemination. The sample consisted of fifth-grade elementary school students from SD Negeri Kajhu, Aceh Besar Regency, who were taught using the gender mainstreaming-based blended learning flipped classroom model. The results showed that the developed learning model created more meaningful learning experiences. Solidarity values and problem-solving abilities of students increased when taught with the learning model.